Benefits of implementing a health and safety management system at work under the ISO 45001: 2018 standard in flower companies to reduce accident - Minchán Yopla, Pedro (2022)
Implementing a Health and Safety Management System at Work under the ISO 45001: 2018 standard has become increasingly important in companies from different sectors, considering that this international standard aims to help organizations establish a safe work environment for the collaborators; On the other hand, the floriculture sector in Peru, which is usually located in Andean areas, is in a period of growth, generating more than 25 thousand jobs. The methodology used in this research was the systematic search of the literature on the implementation of the ISO 45001: 2018 standard in different companies, where the benefits were identified: Preliminary diagnosis of the STT situation, Control and monitoring of the security plan, reduction accident rate, Increase productivity and Improvement of working conditions for employees, achieved after its implementation; Despite these identified benefits, this standard is not yet applied in the floriculture sector.